Transformational Leadership in Human Resources Development to Improve Education Quality in Min 9 Blitar and Mi Wakhid Hasyim Blitar - Mutho'i, Ibadul; Akhyak, Akhyak; Ni'am, Syamsun; Naim, Ngainun; Safi'i, Asrop; Maftukhin, Maftukhin (Technium Social Sciences Journal, 2021)
Transformational leadership is an effort to improve the quality of educational institutions. Transformational leadership is an effort to move educational organizations / institutions to achieve educational goals with all transformational attributes. These attributes are packaged in the form; efforts to establish a vision-mission or set the direction of the school, efforts to develop human resources (HR), and transformational leadership efforts in redesigning the organization. This phenomenon raises an idea in the form of transformational leadership in improving the quality of education with all its attributes. This research uses a qualitative approach, a type of case study with a multi-case design. The results showed that transformational leadership in developing human resources was carried out by increasing the level of higher education, workshop activities, training and competency improvement training, religious motivation, performance appraisal, fingerprinting, good examples, external tutors, adding authority and position.